Safety and efficacy of a molybdenum compound (E7) sodium molybdate dihydrate as feed additive for sheep based on a dossier submitted by Trouw Nutrition International B.V. (27th February 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on safety and efficacy of sodium molybdate dihydrate for sheep, based on a dossier submitted for the re‐evaluation of the additive. The additive is currently authorised in the EU for all animal species as 'Nutritional additive' – 'Compounds of trace elements'. Taking the optimal Cu:Mo ratio of 3–10, and the highest total copper level authorised in complete feeds for sheep (15 mg/kg), the FEEDAP Panel concluded that 2.5 mg total Mo/kg complete feed is safe for sheep. Considering (i) a safe intake of 0.6 mg Mo/day, (ii) the estimate average intake figure from food in Europe (generally less than 100 μg/day), (iii) the contribution of foods of animal origin to the total molybdenum intake (estimated to be up to 22 %), and (iv) that molybdenum would not accumulate in edible tissues/products of sheep fed molybdenum supplemented diets up to the upper safe level, the FEEDAP Panel concluded that the use of sodium molybdate as a additive in sheep at 2.5 mg total Mo/kg complete feed is safe for consumers. The additive under assessment feed poses no risk by inhalation to users; it is a skin and eye irritant, but it is not considered as a skin sensitiser. Sodium molybdate used up to 2.5 mg Mo/kg complete sheep feed poses no concerns for the safety for the environment. The FEEDAP Panel recognises that molybdenum does not need to be added to diets to cover the nutritional needs of molybdenum of sheep. Molybdenum supplementation in sheep feed is considered effective in order to guarantee an adequate balance with copper, when the Cu:Mo ratio in the diet is in the range 3–10.